Like parent, like child? Development of prejudice and tolerance towards immigrants. (19th February 2015) - Miklikowska, Marta
Abstract : Although intergroup attitudes are assumed to develop due to the influence of parents, there is no longitudinal evidence supporting this claim. In addition, research on socialization of intergroup attitudes has omitted possible effects of adolescents on their parents. We also know little about the conditions under which intergroup attitudes are transmitted. This two‐wave, 2 years apart, study of adolescents ( N = 507) and their parents examined the relations between parents and adolescents' prejudice and tolerance from a longitudinal perspective. The study tested whether parental prejudice and tolerance would predict over‐time changes in adolescents' attitudes and whether adolescents' prejudice and tolerance would elicit changes in parental attitudes. Additionally, it explored whether some of the effects would depend on perceived parental support. Results showed significant bidirectional influences between parents and adolescents' attitudes. In addition, adolescents who perceived their parents as supportive showed higher parent–adolescent correspondence in prejudice than youth with low parental support. These findings show that intergroup attitudes develop as a result of mutual influences between parents and adolescents. Hence, the unidirectional transmission model and previous research findings should be revisited. The results also suggest that parents' prejudice influence adolescents' attitudes to the extent that youth perceive their parents as supportive.